2020
DOI: 10.1111/fcsr.12374
|View full text |Cite
|
Sign up to set email alerts
|

Millennials’ Future Homeownership and the Role of Student Loan Debt

Abstract: The financial burden of student loans on individuals in the Millennial generation is a serious issue. We investigated the effect this financial burden has on not only current homeownership but also the expectations and timing for future homeownership. The data came from the 2016 UF/VT Millennial Housing and Student Debt Survey of 1,327 young adults aged 19 to 35. We used a logistic regression model to determine differences in current homeownership and a two‐stage Cragg model to examine the expectation and timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Similar research suggests that renting in desirable areas is preferred to homeownership elsewhere (Pawson, Hulse, and Morris, 2017). Furthermore, student debt has negatively impacted homeownership among millennials (Brown et al, 2015;Cho, Xu, and Kiss, 2015;Houle and Berger, 2015;Mountain et al, 2020;Shand, 2007). As the most educated generation, "millennials are either avoiding homeownership because they do not wish to take on additional debt, or they are unable to get approval for a mortgage due to their high debt loads and poor credit scores" (Xu et al, 2015, pp.…”
Section: Millennials and Homeownershipmentioning
confidence: 89%
“…Similar research suggests that renting in desirable areas is preferred to homeownership elsewhere (Pawson, Hulse, and Morris, 2017). Furthermore, student debt has negatively impacted homeownership among millennials (Brown et al, 2015;Cho, Xu, and Kiss, 2015;Houle and Berger, 2015;Mountain et al, 2020;Shand, 2007). As the most educated generation, "millennials are either avoiding homeownership because they do not wish to take on additional debt, or they are unable to get approval for a mortgage due to their high debt loads and poor credit scores" (Xu et al, 2015, pp.…”
Section: Millennials and Homeownershipmentioning
confidence: 89%
“…Mountain et al. (2020) collected data from Millennials using an online survey. With logistic regression and Cragg two‐part regression models, they found that student loans negatively affected the current ownership rates.…”
Section: Resultsmentioning
confidence: 99%
“…Mountain et al. (2020) surveyed Millennials on the effect of student loan debt and the timing of future homeownership.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations